River Care Community and Padang Disaster Education Park for Disaster Mitigation - Rika Rubianti; Azmi Fitrisia (Pascasarjana, Universitas Negeri Padang, 2019)
This research is motivated to find out the survival of the Society survival in areas prone to landslides In The Village Of North TandikekPatamuan Sub-District, Padang Pariaman District. Research location in the village of North Tandikek. This research uses qualitative approaches with case study research types, data collection techniques by observation, interviews and documentation.The selection of informant is done by Purposive Sampling. The Analysis of this research uses functional structural theory by Talcott Parsoons AGIL. The results of the research are that (1). The reasons for society to stay in the research site are: a). Environmental Factors, b) Economic Factors, c) Social Cultural Factors, d) Education Factors. (2). Society strategies for survival in landslide prone areas that is: a). Looking for a safe haven b). Greening empty land c). Mutual Cooperatin West Sumatra is one area with a high level of disaster vulnerability. West Sumatra BPBD said that West Sumatra was very vulnerable to natural disasters, and for most of the year natural disasters struck. The efforts made by the government in disaster management efforts in West Sumatra, especially in the city of Padang, were to establish a Disaster Education Park on the Purus Coast of Padang City. The Disaster Education Park aims to provide an understanding of disasters to the community, so that the community can prepare themselves for disasters. The purpose of this research is to describe the role of Purus Padang River Care Community and Disaster Education Park for disaster mitigation in Padang City. The method used in this study is a qualitative method with a descriptive approach. The results of this study concluded that there are several roles of the River Concern Community and Disaster Education Park in disaster mitigation efforts in the city of Padang, including: (1) Providing reading books as a source of knowledge about disaster, (2) Establish a River School, (3) Making KPS management a playground, (4) Providing Disaster Material / Training to the Community, (5) Monitor River Development, (6) Maintain the cleanliness of rivers, lakes and beaches.